Unpacking the relationships between conflicts and team innovation: Empirical evidence from China. Issue 8 (20th August 2014) - He, Yuanqiong; Ding, Xiu-Hao; Yang, Kunpeng
Abstract : Purpose: Teamwork is important for innovation, but it often incurs conflicts. Previous literature has reported inconsistent relationships between conflicts and team performance. This study tries to clarify this relationship and explores how to improve team innovation using conflict management styles. Design/methodology/approach: This study collects data in China and the survey covering 436 participants from 126 project teams. Then, structure equation model by AMOS and moderated regression analyses are used for hypotheses testing. Findings: This study finds that cognitive conflict and affective conflict have positive and negative effects on team innovation separately, and cognitive conflict positively affects affective conflict, with the total effect of cognitive conflict on team innovation being negative. Moreover, this study suggests that cooperative conflict management styles and dominating style (one of competitive conflict management styles) moderate the relationship between cognitive conflict and affective conflict negatively and positively. Research limitations/implications: First, this study didn't consider features of organizations as control variables. Future research can advance in this direction. Second, the data was collected from a single marketing innovation program. Further research might use more diversified teams to test the hypotheses. Practical implications: Firms should realize that cognitive conflict promotes team innovation directly, but it also harms team innovation through affective conflict. Then, cooperative conflict management styles are effective in weakening the relationship between cognitive conflict and affective conflict. Originality/value: This study fulfills an identified need to clarify the relationship between conflict and team performance, as well as how conflict management styles moderating the relationship between cognitive conflict and affective conflict.